2018
DOI: 10.2337/dc17-2285
|View full text |Cite
|
Sign up to set email alerts
|

Incretin-Based Therapies and Diabetic Retinopathy: Real-World Evidence in Older U.S. Adults

Abstract: Our population-based cohort study of older U.S. adults with diabetes suggests that IBTs used for approximately 1 year do not increase the DR risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…Our analysis of the FAERS database indicates that there is no signal for the association between GLP-1RA and DR, which is consistent with the Exenatide Study of Cardiovascular Event Lowering (EXSCEL) and Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results (LEADER) trials and our recent cohort study ( 1 ). A recent FAERS analysis ( 2 ) comparing GLP-1RA with other GLDs and stratified by insulin also suggested no signal.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Our analysis of the FAERS database indicates that there is no signal for the association between GLP-1RA and DR, which is consistent with the Exenatide Study of Cardiovascular Event Lowering (EXSCEL) and Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results (LEADER) trials and our recent cohort study ( 1 ). A recent FAERS analysis ( 2 ) comparing GLP-1RA with other GLDs and stratified by insulin also suggested no signal.…”
supporting
confidence: 86%
“…Other trials of glucagon-like peptide 1 receptor agonists (GLP-1RA) showed a numerically higher incidence of DR AEs for liraglutide but not exenatide. However, these trials did not systematically assess DR. Our population-based cohort study of older U.S. adults suggested that GLP-1RA use for approximately 1 year does not increase DR risk ( 1 ). As current evidence on GLP-1RA–associated DR risk is still limited, we conducted a disproportionality analysis of the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database to examine the association between GLP-1RA and DR events.…”
mentioning
confidence: 99%
“…The presence of risk factors, such as smoking, in claims data has high specificity but low sensitivity (35). However, Wang et al (36) have demonstrated that clinical measures such as hemoglobin A 1c are well balanced between DPP4i versus SU and DPP4i versus TZD comparisons in their ACNU study.…”
Section: Limitationsmentioning
confidence: 98%
“…With Type 2 Diabetes (SUSTAIN-6) showed an increased risk of diabetic retinopathy complications associated with semaglutide versus placebo among patients with a history of retinopathy, especially among those with insulin use (1). Although concerns have been raised regarding the safety of glucagon-like peptide 1 (GLP-1) receptor agonists in patients with existing retinopathy, subgroup analyses by retinopathy status at baseline have not been presented for other trials of GLP-1 receptor agonists; the two observational studies on GLP-1 receptor agonists and diabetic retinopathy performed to date have excluded patients with a history of retinopathy (2) or treatment of retinopathy (3).…”
Section: Post Hoc Analyses Of the Trial To Evaluate Cardiovascular Anmentioning
confidence: 99%